Advanced Information Systems Engineering 22nd International Conference, CAiSE 2010, Hammamet, Tunisia, June 7-9, 2010. Proceedings - Pernici, Barbara; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 22nd International Conference on Advanced Information Systems Engineering, CAiSE 2010, held im Hammamet, Tunisia, in June 2010. The 39 papers presented were carefully reviewed and selected from 299 submissions. The topics covered are business process modeling, information systems quality, service modelling, security management, matching and mining, case studies and experiences, conceptual modelling, adaptation, requirements, and process analysis. In addition this volume contains two keynote papers and the abstract of a panel discussion.
Keynotes -- Search Computing Systems -- The Influence of IT Systems on the Use of the Earth$1 (Bs Resources -- Session 1: Business Process Modeling -- Design and Verification of Instantiable Compliance Rule Graphs in Process-Aware Information Systems -- Success Factors of e-Collaboration in Business Process Modeling -- Beyond Process Mining: From the Past to Present and Future -- Session 2: Information Systems Quality -- Dependency Discovery in Data Quality -- Rationality of Cross-System Data Duplication: A Case Study -- Probabilistic Models to Reconcile Complex Data from Inaccurate Data Sources -- Session 3: Service Modelling -- Monitoring and Analyzing Service-Based Internet Systems through a Model-Aware Service Environment -- Modeling and Reasoning about Service-Oriented Applications via Goals and Commitments -- Conceptualizing a Bottom-Up Approach to Service Bundling -- Session 4: Security and Management -- Dynamic Authorisation Policies for Event-Based Task Delegation -- A New Approach for Pattern Problem Detection -- Comparing Safety Analysis Based on Sequence Diagrams and Textual Use Cases -- Session 5: Matching and Mining -- Feature-Based Entity Matching: The FBEM Model, Implementation, Evaluation -- Dealing with Matching Variability of Semantic Web Data Using Contexts -- GRUVe: A Methodology for Complex Event Pattern Life Cycle Management -- Supporting Semantic Search on Heterogeneous Semi-structured Documents -- Query Ranking in Information Integration -- Session 6: Case Studies and Experiences -- Validity of the Documentation Availability Model: Experimental Definition of Quality Interpretation -- Emerging Challenges in Information Systems Research for Regulatory Compliance Management -- Experience-Based Approach for Adoption of Agile Practices in Software Development Projects -- Coordinating Global Virtual Teams: Building Theory from a Case Study of Software Development -- Information Systems Evolution over the Last 15 Years -- Session 7: Conceptual Modelling -- From Web Data to Entities and Back -- Transformation-Based Framework for the Evaluation and Improvement of Database Schemas -- Reverse Engineering User Interfaces for Interactive Database Conceptual Analysis -- Towards Automated Inconsistency Handling in Design Models -- Session 8: Adaptation -- Dynamic Metamodel Extension Modules to Support Adaptive Data Management -- Supporting Runtime System Evolution to Adapt to User Behaviour -- Interaction-Driven Self-adaptation of Service Ensembles -- Session 9: Requirements -- On the Semantics of the Extend Relationship in Use Case Models: Open-Closed Principle or Clairvoyance? -- Situational Evaluation of Method Fragments: An Evidence-Based Goal-Oriented Approach -- Incorporating Modules into the i* Framework -- Ahab$1 (Bs Leg: Exploring the Issues of Communicating Semi-formal Requirements to the Final Users -- The Brave New World of Design Requirements: Four Key Principles -- Session 10: Process Analysis -- The ICoP Framework: Identification of Correspondences between Process Models -- Process Compliance Measurement Based on Behavioural Profiles -- Business Trend Analysis by Simulation -- Workflow Soundness Revisited: Checking Correctness in the Presence of Data While Staying Conceptual -- Panel -- Octavian Panel on Intentional Perspectives on Information Systems Engineering.s
Keywords: Computer science; Computer Communication Networks; Software engineering; Database management; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Computer Communication Networks; Software Engineering; Database Management; Artificial Intelligence (incl. Robotics).